Optimalisasi Reboisasi Mangrove dan Eduwisata Kampung Nipah Untuk Peningkatan Ekonomi Masyarakat Pesisir - Irwadi, Irwadi; Marviana, Ratna Dina; Pratama, Ikbar; Zulkarnain, Mierna; Atrizka, Diny; Zulyadi, Rizkan; Ritonga, Syafruddin; Frensh, Wenggedes (JPM: Jurnal Pengabdian Masyarakat, 2026)
This community service program aims to enhance the coastal community's economic capacity through the integration of mangrove reforestation and the development of educational tourism (edutourism) in Kampung Nipah, Serdang Bedagai Regency, North Sumatra. The community faced several problems, including limited knowledge about mangrove ecosystems, lack of conservation experience, and underdeveloped coastal tourism potential. The program adopted a participatory approach and hands-on training methods. Survey results showed a significant increase in participants’ understanding of mangroves, shifting from mostly low and moderate categories before the program to entirely moderate and high levels afterward. Furthermore, 100% of participants expressed satisfaction with the activities. The program also led to new economic initiatives such as the establishment of a local edutourism management group, tour guiding training, and the development of derivative mangrove products. In conclusion, the program effectively empowered the community both ecologically and economically, despite certain limitations related to time constraints and limited participant reach. Further assistance is recommended to ensure the sustainability of the program’s outcomes.